The “Elderly” Lesson in a “Stressful” Life: Italian Holistic Approach to Increase COVID-19 Prevention and Awareness - Angelini, Sabrina; Pinto, Alessandro; Hrelia, Patrizia; Malaguti, Marco; Buccolini, Fabio; Donini, Lorenzo Maria; Hrelia, Silvana (Frontiers in Endocrinology, 2020)
It’s a frightening time due to COVID-19, but the great elderly/centenarians, apparently more frailty, seem to have approached the pandemic better. “The South Italy” lifestyle seems an “effective strategy” promoting the well-being embedded in a holistic solution: healthy diet, less exposure to PM10 pollution, protected environment, moderate physical activity. The European FP7 Project RISTOMED results, since 2010 have shown that dietary intervention improved a heathy status in the elderly people. Based on the RISTOMED results, in addition to socio-cultural and environmental factors, the Authors suggest an integrated approach for resilience to COVID-19. Such approach along next months could make the difference for the success of any government progress policy to fight COVID-19 finalising long-term well being and successful ageing.